Refusing Medication Therapy in Involuntary Inpatient Treatment—A Multiperspective Qualitative Study - Jaeger, Susanne; Hüther, Franziska; Steinert, Tilman (Frontiers in Psychiatry, 2019)
Objective: From June 2012 to February 2013 two decisions by the Federal Constitutional Court in Germany restricted the so far common practices of using involuntary medication treatment in inpatients who were involuntarily hospitalized. Up to then, involuntary medication was justified by a judge’s decision on involuntary hospital stay and could be applied according to clinical judgment even against the declared will of a patient in those cases. Since then, all domestic laws related to involuntary treatment had to be revised. In an interim time of several months, involuntary medication was only allowed in case of emergency. We were interested in how these limitations affected the experiences of patients, their relatives, and the clinical professionals during that time Methods: 32 interviews were analyzed qualitatively using a Grounded Theory Methodology framework. Results: As a result of the restrictions to involuntary medical treatment special efforts by nursing and medical staff and relatives were required in terms of de-escalation, ward management, promotion of trust and treatment commitment, and coping with the idiosyncrasy and the obvious lack of insight in patients. The family carers were quite concerned about their ill family member and wanted to protect him or her, but at the same time they often welcomed the use of coercion if the patient seemed to lack insight into the condition. Most of the interviewed patients did not perceive their new freedom to refuse medication as such but rather complained about the general limitations they were subjected during involuntary hospitalization. While patients and family members assessed the refusal of medication from a biographical perspective, the mental health care professionals’ focus was on the patients’ symptoms and they understood the situation from a professional perspective. It was obvious that in any of the four perspectives the problem of feeling restricted was crucial and that all groups strived to gain back their freedom of action. Conclusion: In order to prevent compulsion and its negative consequences in inpatient treatment it is indispensable to be aware of the diverging perspectives and to elaborate cooperative and client-centered treatment structures.